Comparing the effects of simulation-based training, blended, and lecture on the simulated performance of midwives in preeclampsia and eclampsia - Maryam Tabatabaeian; Masoumeh Kordi; Salameh Dadgar; Habibollah Esmaeily; Talat Khadivzadeh (Wolters Kluwer Medknow Publications, 2018)
INTRODUCTION: Preeclampsia is the most common medical complication in pregnancy; along with bleeding and infection, it is one of the three causes of death in pregnant women. Most of these deaths were due to delays in the diagnosis and improper midwifery management and care. On the other hand, the quality of midwifery education has a profound effect on the proper provision of services. Therefore, the present study has been done to compare the effect of simulation-, blended-, and lecture-based education on simulated midwife performance in the management of preeclampsia and eclampsia. MATERIALS AND METHODS: This three-group clinical trial study was performed on 90 midwives of selected hospitals in Mashhad in 2016. Midwives were divided into three groups of simulation-, blended-, and lecture-based education using the random number table. The simulation group was trained for 6 h at the Center for Clinical Skills, the blended group was trained for 4 h by lecture, and 6 weeks through the educational website, and the lecture group was trained for 6 h through lecture. An objective structured clinical test was performed before and 2 weeks after the intervention. Data were analyzed using SPSS Version 16 software and descriptive statistics, paired t-test, one-way ANOVA, and Wilcoxon and Kruskal-Wallis tests. Significance level was considered to be P < 0.05 in all cases. RESULTS: The mean score of midwives' performance was not statistically significant before education in all three groups (P < 0.05). The mean score of midwives' performance was significantly increased in all three groups 2 weeks after education (P < 0.001), and the results of intergroup comparison showed that the mean score of performance in the simulation group was significantly higher than the blended group and the lecture group (P < 0.001), and it was higher in the blended group compared to the lecture group (P < 0.001). CONCLUSION: Education increased the midwives' simulated performance in preeclampsia and eclampsia. The performance of the management of preeclampsia and eclampsia in the simulation educational group is more than that of the blended and lecture groups, so we can use the simulation education which is a self-centered method.